Examining How Culturally Responsive Teaching Affects Student Involvement and Academic Performance in Multicultural Classrooms - Zaki Ul Ilmi; Nurfadila; Abdal Ahmed (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
This study explores the impact of culturally responsive pedagogy (CRP) on student engagement and academic performance in multicultural classrooms. As educational environments become increasingly diverse, CRP has emerged as a critical approach to meet the needs of students from various cultural backgrounds. This quasi-experimental study involved students from multicultural classrooms across multiple schools, with one group implementing CRP strategies and a control group using traditional teaching methods. Data was collected through surveys assessing student engagement and academic records to measure performance before and after the implementation of CRP practices. The findings indicate that students in CRP classrooms exhibited significantly higher engagement levels and improved academic performance compared to the control group. The increased student participation, motivation, and academic success were attributed to the integration of culturally relevant content that resonated with students’ cultural identities. The study highlights several challenges in the implementation of CRP, including the need for professional teacher training, curriculum adaptation to incorporate cultural relevance, and strong policy support. It also underscores the importance of teacher preparedness, curriculum adaptation, and institutional support in ensuring the effective implementation of CRP. The study’s results align with international best practices, demonstrating that CRP significantly enhances student outcomes, particularly among minority cultural groups. Future research should focus on the long-term effects of CRP and its scalability across various educational contexts to further understand its impact on academic achievement and engagement in diverse classroom settings.